2015
DOI: 10.2147/copd.s92133
|View full text |Cite
|
Sign up to set email alerts
|

Health care and social care costs of pneumonia in Denmark: a register-based study of all citizens and patients with COPD in three municipalities

Abstract: BackgroundPneumonia is a frequent lung infection and a serious illness, which is often diagnosed among patients hospitalized with acute exacerbations of COPD. The aim of this study was to estimate the attributable costs due to pneumonia among patients hospitalized with pneumonia compared to a matched general population control group without pneumonia hospitalization.MethodsThis study includes citizens older than 18 years from three municipalities (n=142,344). Based on national registers and municipal data, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…However, the median LOS was 4-6 days, which is in line with a recent report on pneumonia cases from the National Quality Register for Infectious Diseases [19]. Furthermore, a Danish study investigated the costs attributable to pneumonia among hospitalized patients and found that the costs increased with age [22], as in the current study.…”
Section: Plos Onesupporting
confidence: 89%
“…However, the median LOS was 4-6 days, which is in line with a recent report on pneumonia cases from the National Quality Register for Infectious Diseases [19]. Furthermore, a Danish study investigated the costs attributable to pneumonia among hospitalized patients and found that the costs increased with age [22], as in the current study.…”
Section: Plos Onesupporting
confidence: 89%
“…In contrast, our meta-analysis revealed that males were 42% more prone to develop post-stroke pneumonia. This sex-difference may reflect an actual incidence disparity between males and females [ 34 , 35 ], possibly driven by higher prevalence of current and past smoking in males in these age groups [ 36 ]. Another possible explanation is that the results may be biased by the well-known relative under-representation of UTI in males, which may prompt the clinician to suspect airway infections rather than UTI in males with post-stoke fever, while suspecting UTI in women.…”
Section: Discussionmentioning
confidence: 99%
“…9 The societal costs of COPD are considerable. 10,11 The estimated annual costs per person for COPD-related health care contacts in Denmark is 8572 EUR. 12 The majority of costs relate to primary care and in-hospital care during exacerbations.…”
Section: Introductionmentioning
confidence: 99%